OVERVIEW OF EXAMINATION STANDARDS AND EVALUATION PROCESS CONDUCTED BY OUT- SOURCED UNIVERSITIES BY PAKISTAN MEDICAL AND DENTAL COUNCIL FOR FOREIGN QUALIFIED MEDICAL PROFESSIONALS IN PAKISTAN - Khan, Samina Mohsin; Mahmood, Raja Amjad (Journal of Ayub Medical College Abbottabad, 2016)
Background: Pakistani nationals that obtained foreign basic/additional medical/dental qualifications need to be registered with Pakistan Medical and Dental Council (PMDC) to serve in health delivery system after qualifying the National Examination Board (NEB) conducted by the outsourced universities. The aim was to analyse the results and the factors that influence the NEB examinations held for accreditation conducted by different universities from the year 2010 to 2015. Methods: The register based data was collected from the NEB section of PMDC for examinations conducted in the year 2010, 2013, 2014 and 2015. The format of the examination comprises three parts that include Step I, II based on written assessment composed of both multiple choice and subjective questions. Step III is designed for oral assessment, i.e., viva voce. All these examination were held in Islamabad conducted by the outsourced universities. Results: The percentage of candidates that has passed all the examinations, Step I, II & III held by various universities varies across the universities. Further, the percentage of passed candidate remains low in Step I & II as compared to candidates passed in Step III. Overall the result of Step III shows a wide gradient that ranges from 50% to 98% among the different universities. Likewise, the lowest percentage of passing candidates in Step I and Step II remains 4% and 9% respectively as compared to 50% in Step III. Conclusion: There is a wide gradient in the results of NEB examination among universities due to lack of uniformity and standardization of assessment process. In addition, with regards to the approach of examination venue, the faced issues include lack of accessibility and cost effectiveness. The PMDC needs to institutionalize a robust and vigorous accreditation system equipped with inbuilt evaluation indicators that should steer to devise strategies to improve the accreditation process.